Penerapan Evaluasi Heuristik pada Perancangan Sistem Point Of Sales Berbasis Website - Ramba, Rileanly Masakke; Fibriani, Charitas (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The Agape Shop in Biak Papua carries out transactions only with receipts and calculators. Shop owners are often overwhelmed with serving customers and experience calculation errors because they still use calculators, have difficulty managing product stock, and have limited information on income and expenses. Therefore, this research will design a website-based Point of Sales (POS) system that can make it easier to manage transactions, product stock, sales reports, etc. The system development method uses the Agile method and heuristic evaluation to evaluate the system's interface. The process of working on a system using Unified Modeling Language (UML) includes Use Case Diagrams; Class Diagram, Entity Relationship Diagram (ERD) database structure design, and User Interface/User Experience (UI/UX) design. Meanwhile, the programming language uses the PHP Laravel framework; JavaScript uses the JQuery library and uses the MySQL database which is used to develop this system. This research produces a website-based Point of Sales (POS) system that makes it easier to manage product stock, transaction management and sales reports.